(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Finance is the various forms of the basic components of the economies of the countries and playing the important role of developing of the social aspects and economic communities, and foreign trade in particular, its really important for countries because finance represent the largest share in the national income. Thus, finance became the important aspects for nations and how could be improved and ensure good reputation to it , Perhaps one of the most important insurance that seek to achieve is the funding guarantees through the intervention of financial institutions and most important banks, using a range of techniques and tools that today are among the most important foreign trade financing sources and the most important documentary credit, which gives a kind from the comfort and safety of the importer and exporter, and ensures both the physical and moral and keep the right for each one